Magnetic hybrid organic–inorganic perovskite (CH3NH3)2XCl4 (X = Mn, Cu, Co) crystals. Issue 30 (9th July 2021) - Zhao, Hongyang; Fu, Haoran; Hu, Zhao; Fu, Qiuming; Tao, Hong; Weng, Jun; Xiong, Liwei; Cheng, Zhenxiang
Abstract : We reported three hybrid organic–inorganic perovskite single crystals of (CH3 NH3 )2 MnCl4, (CH3 NH3 )2 CuCl4 and (CH3 NH3 )2 CoCl4 . Magnetic measurements show that all the single crystals display magnetic ordering at low temperature. Abstract : For the hybrid organic–inorganic perovskites with the general formula of A2 M II X4 (A = methylammonium; M II = Mn, Cu and Co; X = Cl), the arrangement of metal ions and organic ligands leads to a delicate balance of space, spin and charge, which results in diverse properties. In this paper, we reported a group of hybrid organic–inorganic perovskite single crystals of (CH3 NH3 )2 MnCl4, (CH3 NH3 )2 CuCl4 and (CH3 NH3 )2 CoCl4 grown by a simple solution evaporation method. Magnetic measurements show that all the single crystals display magnetic ordering at low temperature. Our results reveal a novel group of hybrid organic–inorganic magnetic perovskites.